IDENTIFIKASI DAYA TAMPUNG BEBAN CEMARAN BOD SUNGAI DENGAN MODEL QUAL2E (STUDI KASUS SUNGAI GUNG, TEGAL – JAWA TENGAH) - Nugraha, Winardi Dwi; Cahyorini, Lintang (Universitas Diponegoro, 2007)
Gung River is a one of the river in Central Java which pass trough Tegal Region with total length about 48 km. The important thing in environmental problems that faced by Gung River such as increasing the load of water pollution. BOD is one of the water pollution indicator in the streams. To make easier in knowing the the amount of Total Maximum Dailly Load (TMDL)in Gung River , it is identified TMDL of BOD uses modeling principal with Qual2E Modelling. And than it is compared with the standar streams due to PP No. 82/2001 about Water Quality Management and Water Pollution Control. The result of simulation due to TMDL uses minimum flow rate is compared with standard stream ini PP 82 / 2001. It indicate that the quality could not meet with the standard stream related with the class 1 and class 2. In Reach 1 ( km 1 – 3 ) could meet with standar stream of class 3 with TMDL 1,43 – 9,98 kg/day. All the stream along the river could meet with standar stream ini class 4 with TMDL of BOD is 7,13 – 865,34 kg / day. The result of simulation due to TMDL uses maximum flow rate is compared with standard stream ini PP 82 / 2001. It indicate that the quality could not meet with the standard stream related with the class 1 and class 2. In Reach 1 ( km 1 – 3 ) could meet with standar stream of class 3 with TMDL 72.06 – 3134,51 kg/day. All the stream along the river could meet with standar stream ini class 4 with TMDL of BOD is 7277,82 – 10.340,27 kg / day.